Kualitas Laporan Keuangan Desa: Suatu Tinjauan Terhadap Faktor-Faktor yang Mempengaruhi Akuntabilitas dan Transparansi - Mila, Shofiatul; Putri, Julia Harita (Jurnal Ekonomika dan Bisnis, 2023)
This research aims to determine the influence of the Internal Control System, Use of Information Technology and Human Resource Competence on the Quality of Village Financial Reports in Patebon District, Kendal Regency. The type of data used in this research is quantitative data. The data collection method in this research uses a questionnaire. The number of samples in this research was 72 village officials who were directly and actively involved. The research instrument used in this research used the Likert Scale method using the Statistical Package the Social Science (SPSS) application. The validity test uses the Pearson product moment correlation test, while the reliability test uses Cronbach Alpha. The data analysis technique used is multiple regression analysis. The research results show that: (1) The Internal Control System has a positive effect on the Quality of Financial Reports (2) The use of Information Technology has no effect on the Quality of Financial Reports (3) Human Resource Competency has a positive effect on the Quality of Financial Reports